Effect of different alcoholic solvents on the structural and electrochemical characteristics of NH4V4O10/carbon sphere composites for hydrogen storage application - Maryam Ghiyasiyan-Arani (Applied Water Science)
Abstract Energy storage devices have recently made extensive use of carbon frameworks. The intention of this investigation is to look at how the carbon sphere (CS) affects NH4V4O10 (NHV) electrode materials for energy storage. Carbon spheres were synthesized via ethylenediamine-based catalyst sonochemical method with resorcinol–formaldehyde (R-F) polymer resin. The incorporation carbon spheres have the potential to enhance the low conductivity of vanadate-based materials. The solvothermal approach was employed to synthesize electrode materials which were designed to possess a three-dimensional (3D) flower-shaped structure by studying the effect of different solvents. The flower-shaped nanoribbon self-assembly structure is present in all samples. The average ribbon thickness from synthesized samples subjected to ethanol, propanol, and butanol was 16, 28, and 23 nm. In comparison to pure NHV, the surface area of the carbon sphere nanocomposites (NHV-EtOH/CS) developed to 17.843 m2g−1. The carbon sphere-based composite material has a capacitance of 295 mAhg−1 by applying I = 1 mA for 15 cycles, which is different from that of pristine NH4V4O10. Therefore, the incorporation of a three-dimensional configuration within the sphere on flower structures holds promise for improving the efficacy of energy storing in electrodes completed of ammonium vanadium-based oxides. The diffusion coefficient for NHV-EtOH was 1.12 × 10–15 cm2/s, while for NHV-EtOH/CS, it was 4.48 × 10–13 cm2/s. Thus, the NHV-EtOH/CS composites exhibited a higher diffusion factor than pure NHV.